Brand ambassadors at the center of the advertising strategy: The launch of Samsung Spain mobile devices with urban music artists - Miguélez-Juan, Blanca; Rebollo-Bueno, Sara (VISUAL REVIEW. International Visual Culture Review / Revista Internacional de Cultura Visual, 2023)
The market is saturated with messages, a multitude of brands and products want to be present in the minds of the youngest consumers. The "app generation" is becoming more and more demanding, however, it is easier to reach them through music and video clips. Samsung's strategy to achieve its goals has been to use two up-and-coming music artists as the brand ambassadors. They have integrated the new smartphone devices into both the music videos and the creation of their songs to organically and directly reach their target audience.